2021
DOI: 10.4014/jmb.2103.03009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phenotypic Analysis of Anabaena sp. PCC 7120 Mutants of Porinlike Genes

Abstract: Porins are essential for the viability of Gram-negative bacteria. They ensure the uptake of nutrients, can be involved in the maintenance of outer membrane integrity and define the antibiotic or drug resistance of organisms. The function and structure of porins in proteobacteria is well described, while their function in photoautotrophic cyanobacteria has not been systematically explored. We compared the domain architecture of nine putative porins in the filamentous cyanobacterium Anabaena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Additionally, some mutants of porin-like genes from Anabaena sp. PCC 7120 had altered phenotypes of the outer membrane, affected integration of other porins in the membrane or affected nitrogen demand and/or fixation (Schätzle et al, 2021). Hence, the OprB family appears to have a diversity of roles in bacterial biology; however, whether the role of OprB in sugar uptake is primary or a secondary effect cannot be distinguished because membrane integrity or integration of other proteins into the membrane was not assessed by Ekman et al in 2013. In agreement with the data from Khamar et al (2010), all mutants for the fructose and glucose transporters were able to form hormogonia (Ekman et al, 2013).…”
Section: Establishment Of Interaction With Cyanobacterial and Other S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some mutants of porin-like genes from Anabaena sp. PCC 7120 had altered phenotypes of the outer membrane, affected integration of other porins in the membrane or affected nitrogen demand and/or fixation (Schätzle et al, 2021). Hence, the OprB family appears to have a diversity of roles in bacterial biology; however, whether the role of OprB in sugar uptake is primary or a secondary effect cannot be distinguished because membrane integrity or integration of other proteins into the membrane was not assessed by Ekman et al in 2013. In agreement with the data from Khamar et al (2010), all mutants for the fructose and glucose transporters were able to form hormogonia (Ekman et al, 2013).…”
Section: Establishment Of Interaction With Cyanobacterial and Other S...mentioning
confidence: 99%
“…Functional analyses of the genome of the symbiotic N. punctiforme showed that it encodes a functional fructose transporter, a glucose permease and an OprB family porin, which was associated with the uptake of both sugars (Ekman et al, 2013 ). In other cyanobacteria, this porin family has recently been associated with transport of different metals (Qiu et al, 2021 ; Schätzle et al, 2021 ). Additionally, some mutants of porin-like genes from Anabaena sp.…”
Section: Recurrent Molecular Patterns In Cyanobacterial Symbioses—a H...mentioning
confidence: 99%
“…2 ; Table S2). This group includes several porin-like proteins, namely the major outer membrane proteins Alr0834 (OprB-1), Alr4741, Alr7614, Alr4893, All4499, Alr4550, and Alr2269 (Omp85) ( 13 , 32 , 33 ); the outer membrane TolC transporter homolog HgdD (Alr2887) ( 34 ); the N-acetylmuramyl-L-alanine amidases AmiC1, AmiC2, and All4999 ( 35 , 36 ); and LptA (Alr4067), a protein of the lipopolysaccharide export system to the outer membrane ( 37 ), among others. Finally, it is noteworthy the strong decrease in the two-component hybrid sensor and regulator All1178 (−451.68-fold), whose function is unknown, and the FurA paralog ( 38 ) (−87.48-fold).…”
Section: Resultsmentioning
confidence: 99%
“…In response to this, different uptake systems and pathways have evolved and their components are encoded in the genomes of cyanobacteria. The transport of solutes involves, for example, porins for salt and other nutrients (e.g., [ 1 – 3 ]). Solutes that exceed the diffusion size of porins or have a very low abundance in the environment are actively transported by specialized systems (e.g., [ 4 ]).…”
Section: Introductionmentioning
confidence: 99%